Student’s Perception on Classroom Management During Online Learning - Agus Rofi’i; Rama Dwika Herdiawan; Ai Rosidah (Jurnal Educatio FKIP UNMA, 2023)
Learning activities are usually carried out face-to-face, but teachers also conduct online learning. Everyone is using technology, and it's easier for students and teachers to communicate. This study aims to describe students' perceptions of classroom management during online learning and find out the obstacles students face. This research uses a descriptive qualitative method. The data collection technique in this study used a questionnaire distributed in the form of a Google form regarding students' perceptions of online English learning. Respondents from semester 6 consisted of 10 students. The results of this study indicate that most students have many obstacles in online learning. Online learning is considered less effective to be applied in the learning process. Therefore, this data proves that research respondents have a negative perception of classroom management used by lecturers in online learning. The results of the study concluded that class management during online learning was not well received by students, so institutions need to make their students more comfortable, and lecturers need to improve class management.